Representations of puns in the cover designs of Der Spiegel magazine (Al-Academy, 2022)
Pun concept the design discourse for the cover of magazines the researcher chose the German magazine Der Spiegel as a model for that, as the research problem was manifested by the following question: What are the representations of puns in the covers of the German magazine (Der Spiegel)? The researcher has identified four chapters for this study as follows: The first chapter is devoted to research procedures, and the theoretical framework, which is like the second chapter, included the literature related to the topic of research according to the two interlocutors. A review of the concept of pun in the field of typographic design and the functions that puns achieve in that field, leading to the third chapter, which included the analysis of sample models, and the fourth chapter (results and conclusions).